Assessment Mixing and Compaction Temperatures for Modified HMA Using Superpave High Shear Viscosity Methods - Abed, Alaa Hussein; Nasser, Ali Hwaidi (Al-Nahrain Journal for Engineering Sciences, 2018)
The objective of this study is determining the mixing and compaction temperature of the modified asphalt mixture. Results of binder tests showed that the addition of 3% SBS to control asphalt (PG 64-16) would achieve the desired performance level (PG 76-16) a performance grade that fits our climate with traffic loads. When using 5% SBS the performance grade of binder increased three grades (PG 82-16) and when increasing SBS content to 8% the performance grade increased four grades (PG 88-16). At shear rate of 500 (s-1), the modified asphalt viscosity can be obtained at different temperatures and the viscosity temperature curve can be achieved. As a result, the mixing and compaction temperature of modified asphalt can be determined to reach 0.17 ± 0.02 Pa.s and 0.28 ± 0.03 Pa.s for mixing and compaction, respectively. It is noted that SBS modified reached a viscosity of 3 Pa.s when 8 % additive. Additive contents above these values may not be suitable for good workability and pump ability according to Superpave specifications. While addition of 5% SBS with control asphalt, more than 3.7times at 135°C Increase the viscosity. Marshall Stability test indicated that the strength for the SBS specimens increases as compared to the conventional specimens. An increase of about 39%, 74%, 102%, was observed with 3%SBS 5%SBS 8%SBS modified binders, respectively. The Marshall test results for 8%SBS binders required compaction temperatures above 175°C need to keep up quality of HMA item while limiting natural effect amid development, these proposals are unsatisfactory Modified mixtures the 5% SBS modification was determined to be the maximum useful content. The Superpave method to estimate mixing and compaction temperatures show are not practical for use with modified binders. Also, it is observed that good agreement values between the average Marshall compaction temperature and the High Shear Viscosity Method (HSRV) and lower than Superpave methods Where the decline ranges from 15 ºC to 17 ºC.